2017
DOI: 10.1016/j.amjcard.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics and Complications in Men Versus Women Undergoing Chronic Total Occlusion Percutaneous Intervention

Abstract: Gender differences exist in clinical outcomes after routine percutaneous coronary intervention (PCI), but studies reporting such outcomes after chronic total occlusion (CTO) PCI are limited. We assessed the characteristics and outcomes of female patients undergoing CTO PCI. We retrospectively analyzed a dedicated national (United Kingdom) prospective CTO database from 2011 to 2015 for outcomes and characteristics of female patients undergoing CTO PCI (unmatched and propensity matched). Female patients constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 32 publications
6
31
5
1
Order By: Relevance
“…Lesion length was shorter in women. There has been discordance in prior studies about procedural success and complication risk of CTO PCI by sex . In this study, procedural success and MACCE rates were similar in both sexes.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Lesion length was shorter in women. There has been discordance in prior studies about procedural success and complication risk of CTO PCI by sex . In this study, procedural success and MACCE rates were similar in both sexes.…”
Section: Discussioncontrasting
confidence: 55%
“…There has been discordance in prior studies about procedural success and complication risk of CTO PCI by sex. 4,8,9 In this study, procedural success and MACCE rates were similar in both sexes. Smaller coronary artery diameters 22 and more tortuous collaterals have been hypothesized as reasons for less success with retrograde CTO PCI in women but in this cohort, sex had no impact on the approach (antegrade vs retrograde) or final successful strategy (wire escalation vs dissection re-entry).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Indeed, there is significant overlap between our cohort with complex co‐morbidities and calcific disease and the chronic total occlusion (CTO) PCI population. A large contemporary CTO registry similarly showed that women suffer more periprocedural complications including coronary perforation and bleeding (women 10.0 vs. men 4.5%, p = .0012) …”
Section: Discussionmentioning
confidence: 97%
“…Of these, 93.6% were older than 50 years. Analyzes conducted in the UK with 1,271 patients found that 79.5% were males and 20.5% females, in view of this, the comparative study shows that 48.1% of the female population had age group over 70 years, whereas in men this percentage was only 28.6% (12) .…”
Section: Discussionmentioning
confidence: 74%